THE EFFECT OF DISCOVERY LEARNING MODEL AND SOCIAL SKILLS ON STUDENT LEARNING OUTCOMES PPKN SUBJECTS IN CLASS V SDN 034799 DOLOKTOLONG - Paska Sriulina Tarigan; Deny Setiawan; Sri Milfayetty (SENSEI RESEARCH CENTER, 2021)
This study aims to determine: 1) The influence of discovery learning and expository learning models on student learning outcomes, 2) The influence of social skills on student learning outcomes. 3) The interaction between learning models and social skills on student learning outcomes. This study used a quasi-experimental research method. The research was conducted from April to May 2021.The population of this study were 48 students of grade V SDN 034799 Doloktolong who were chosen randomly by random sampling technique. The sample is the VA class as many as 24 people as the experimental class and the VB class as many as 24 people as the control class. Data collection techniques using social skills questionnaires and learning outcomes tests. The data analysis technique used two-way analysis of variance. The results of the study are as follows: (1) There are differences in learning outcomes students who were taught with the discovery learning model with an average value of 85,556 higher than the learning outcomes of students taught by the expository learning model with an average of 76,944, the results of the analysis of variance showed that the Fcount value was 71.11> the Ftable value was 3.20 and the probability or significance value 0.00 <0.05, so H0 is rejected; (2) There is a significant difference between the learning outcomes of students with high social skills and the average84,364and students who have low social skills on average 67.00. Result of analysis of variance obtained Fcount value of 17.35> Ftable value of 3.20 and a significant value of 0.017 <0.05, so that H0 is rejected; (3) There is an interaction between discovery learning models and students social skills in improving student PPKn learning outcomes, the results of analysis of variance Fcount value of 6,021> Ftable value of 3.20 and a significance of 0.018 <0.05, so that H0 is rejected.